ANALISIS KESELAHAN EJAAN PADA TEKS EKSPOSISI DALAM PEMBELAJARAN BAHASA INDONESIA KELAS X SMA NEGERI 2 LINGGO SARI BAGANTI - Riska Mayeni; Revi Handayani; Septiana Vratiwi; Sefrinal Sefrinal (STKIP Pesisir Selatan, 2022)
This research started from the fact that there were many spelling errors that were not in accordance with the spelling rules that applied to students' work in writing exposition texts at SMAN 2 Linggo Sari baganti. Thus, it is necessary to conduct a study in the form of an analysis of spelling errors on students' writing results. The purpose of this study was to find out the forms of errors in the use of Indonesian spelling in the exposition texts of class X SMA students along with the stages and forms of justification and to find out the causes of errors in the use of Indonesian spelling in the exposition texts of students' works. This study uses a qualitative type of research using the descriptive method with the aim of analyzing Indonesian spelling errors that appear in exposition texts by class X SMA students. The population in this study amounted to 66 consisting of 22 data sources for class X1 SMA, 22 class X2, and 22 class X3. The data collection used a purposive sampling technique with data collection techniques using observation, interviews, and documents. The results of the study found 476 spelling errors used by class X students of SMAN LISBA in writing exposition texts. In the use of capital letters with an error of 250 with a percentage of 47%, then errors in writing compound words 5 with a percentage of 1%, errors in writing derivative words 70 with a percentage of 10%, errors in writing prepositions of 40 with a percentage of 6%, use of full stop punctuation errors a number of 90 15%, errors in the use of comma punctuation a number of 111 with a percentage of 16%.